The emerging role of exosomes in the pathogenesis, prognosis and treatment of necrotizing enterocolitis - Chen, Wenjuan (Am J Transl Res, 2020)
Exosomes are a subtype of extracellular vesicles. They contain bioactive molecules, including nucleic acids, proteins and lipids. Among the currently described exosomes, a majority are potential candidates for the diagnosis and treatment of necrotizing enterocolitis (NEC). In this work, we reviewed existing literature reports on exosomes and explored their roles in NEC. Exosomes derived from intestinal epithelial cells (IECs) participates in the development of intestinal diseases, thus can potentially be utilized as biomarkers for NEC. Besides, exosomes of human milk have been demonstrated to protect IECs from oxidative stress, stimulate intestinal stem cells activity, improve the proliferation and migration of IECs, and lower the incidence and severity of experimental NEC. Further, exosomes produced by stem cells can reduce the severity of experimental NEC and protect the intestinal barrier function during NEC. Conclusively, exosomes have been shown to influence the pathogenesis of NEC and exert a protective effect on NEC. However, additional investigations would be urgently necessary to comprehensively elucidate the underlying mechanisms of exosomes in NEC.